Histopathology of Chironomus riparius (Diptera, Chironomidae) exposed to metal oxide nanoparticles - Stojanović, Jelena S.; Milošević, Đurađ D.; Vitorović, Jelena S.; Savić Zdravković, Dimitrija N.; Stanković, Nikola R.; Stanković, Jelena B.; Vasiljević, Perica J. (Archives of Biological Sciences, 2021)
Paper description: Chironomus riparius is a model organism in ecotoxicology. Histological analysis of its internal morphology could help identify biomarkers of the effects of sublethal concentrations of pollutants. 4th instar larvae of riparius were exposed to sublethal concentrations of TiO2, CeO2 and Fe3O4 nanoparticle and histological analysis was performed. Nano-Fe3O4 and nano-Fe3O4/nano-CeO2 exposure caused vacuolization of epithelial cells of midgut region I and Malpighian tubules, respectively; nano-TiO2 exposure altered fat body and midgut region II tissue architecture; nano-Fe3O4 shortened the intestinal brush border. The identified histopathological biomarkers of riparius larvae improve existing methodology in water quality assessment. Abstract: As the production of metal-based nanomaterials increases, it is inevitable that nano-scale products and byproducts will enter the aquatic environment. In terms of global production, the most abundant nano-oxides are TiO2, CeO2 and Fe3O4 nanoparticles. Chironomus riparius is commonly used for ecotoxicological assessment and defining its histopathological biomarkers that showcase the toxic effect of tested nanoparticles should lead to a better understanding of the consequences of nanomaterial accumulation in aquatic ecosystems. In this study, a histological description of the digestive and excretory systems as well as the fat body structure of C. riparius larvae is provided. In addition, potential histological biomarkers of nano-oxide toxicity were determined based on the obtained histopathological alterations in organs. Vacuolization was observed in epithelial cells of midgut region I that were treated with nano-Fe3O4 as well as in Malpighian tubules treated with nano-Fe3O4 and nano-CeO2. Larvae exposed to nano-TiO2 showed alterations in the fat body and midgut region II tissue architecture. Additionally, shortening of the intestinal brush border was determined in groups exposed to nano-Fe3O4. These results reveal the high sensitivity of these organs, which can be used as biomarkers in histopathological assessment and therefore lead to further improvement of existing methodology in ecotoxicological studies.